Changes in the Swedish society 1976 - Postal survey - Himmelstrand, Ulf (Uppsala University, 1984)
The study tries to find out what interaction there is between employees working situation and working conditions and their perception of and attitudes towards different types of changes in society. The study is made in two steps, first all 1294 respondents answered the questionnaire and then 164 of them were interviewed in the second step.

Syftet med undersökningen var att kartlägga vilka samband som finns mellan anställdas arbetssituation/arbetsförhållanden och deras uppfattning av och inställning till olika typer av samhällsförändring. En viktig del av undersökningen var utnyttjandet av s.k. hotbilder. Materialet samlades in i två steg, där det första utgörs av ett frågeformulär som besvarades av 1294 respondenter. I steg två genomfördes intervjuer med 164 av respondenterna i steg ett.
Samhällsförändring i Sverige 1976 - Enkätundersökningen
Keywords: employment; anställning; groups; grupper; wages; löner; standard of living; levnadsstandard; hazards; faror; trade unions; fackföreningar; working conditions; arbetsförhållanden; leisure time activities; fritidsaktiviteter; commuting; pendling; Working conditions; Arbetsförhållanden; Social behaviour and attitudes; Socialt beteende och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap